IMPACT OF MAGNETIC RESONANCE IMAGING ON HEMATOLOGICAL PARAMETERS ON ALBINO MICE - Amuda, Dauda Biodun; Babalola, Bolaji Oluwatoyin; Oni, Emmanuel Abiodun; Oguntunji, David Bolawa; Oyedepo, Victor Olufemi; Bello, Temitope Olugbenga; Gilbert, Celestine Etumonu; Oni, Olatunde Micheal; Olarinoye, Ismail Oyeleke (FUDMA JOURNAL OF SCIENCES, 2024)
Magnetic resonance imaging (MRI) is a non-invasive technique that uses strong magnetic fields and radiofrequency radiation, to measures behaviour of atomic nuclei inside the body, producing signals that are used to create images. The interactions between the biological systems and magnetic fields present in MRI, concerning changes in hematological parameters are not understood. This research investigated the effects of MRI on hematological parameters in albino mice. 30 male albino mice were divided into two groups, A (control) and B (exposed), each consisting of 15 mice. Mice in group B were exposed to a 1.5 T MRI scanner once a week for 30 minutes for 3 weeks. After the first exposure 5 mice from the exposed and 5 mice from the control were deeply sedated. This was repeated in the second and third exposure. Ministry of Health in Oyo State approved all protocols for animal experimentation. Data were expressed in mean ± standard error (S.E.) and analyzed using GraphPad Prism. First week of exposure indicated a significant increase in packed cell volume, neutrophils, lymphocytes, monocytes of the exposed group except for white blood cells which decreased. There was significant decrease in packed cell volume and lymphocytes of the exposed group except for white blood cells and Neutrophil which increased, monocytes were not significant in the second week. Third week indicated significant increase in white blood cell, lymphocytes, monocytes except for packed cell volume and Neutrophil which decreased. Thus, the hematological parameters of albino mice are negatively impacted by MRI exposure.